The concept of treatment-free remission in chronic myeloid leukemia - Saußele, Susanne (Leukemia, 2016)
The advent of tyrosine kinase inhibitors (TKI) into the management of patients with chronic myeloid leukemia (CML) has profoundly improved prognosis. Survival of responders is approaching that of the general population but lifelong treatment is still recommended. In several trials, TKI treatment has been stopped successfully in approximately half of the patients with deep molecular response. This has prompted the development of a new concept in the evaluation of CML patients known as ‘treatment-free remission’. The future in CML treatment will be to define criteria for the safe and most promising discontinuation of TKI on one hand, and, on the other, to increase the number of patients available for such an attempt. Until safe criteria have been defined, discontinuation of therapy is still experimental and should be restricted to clinical trials or registries. This review will provide an overview of current knowledge as well as an outlook on future challenges.
Gesehen am 13.08.2019